Weak Hypoxia Enhanced Denitrification in a Dissimilatory Nitrate Reduction to Ammonium (DNRA)-Dominated Shallow and Eutrophic Coastal Waterbody, Jinhae Bay, South Korea - Huang, Yan; An, Soonmo (Frontiers in Marine Science, 2022)
The effects of seasonal hypoxia on sediment-water interface nitrogen (N) transformations in Jinhae Bay were examined from 2015 to 2019. The rates of benthic denitrification, anaerobic ammonium oxidation (anammox), dissimilatory nitrate reduction to ammonium (DNRA), nutrient exchange, and sediment oxygen consumption were measured seasonally. The oxygen (O2) and hydrogen sulfide (H2S) depth profiles were measured using microelectrodes. Neither penetration nor consumption of oxygen decreased during hypoxia. Denitrification, anammox, and DNRA ranged from 0 to 0.73, 0.13, and 1.09 mmol N m-2 day-1, respectively. Denitrification, the dominant N removal pathway, increased by 75% while anammox ceased, which led to an overall increase of 55% in the total N2 gas production during hypoxia relative to that during normoxia. Enhanced denitrification is the result of increased coupled nitrification–denitrification due to the intermittent supply of oxygen during bottom water hypoxia (“weak hypoxia”). In the hypoxic period, DNRA decreased by 62%, and the relative contribution of DNRA to the total nitrogen reduction process decreased from 81 to 58%, but it still outperformed denitrification as the main nitrate reduction pathway. Sediments were strong sources of ammonium for the water column, both under normoxia and hypoxia, whereas they were a sink of nitrate from the water column during hypoxia. Bioturbation may be important for maintaining oxygen penetration and consumption in sediments. The dominance of DNRA was mainly due to the relatively high content of sulfide and organic-rich sediments. The repressed macrofaunal activity and increased coupling of nitrification and denitrification during hypoxia may have contributed to enhanced denitrification. Taken together, the overall dominance of DNRA might contribute to the development and maintenance of eutrophication and seasonal hypoxia in this system. However, in contrast to the previous results, denitrification was enhanced during “weak hypoxia,” which might be helpful in alleviating eutrophication.